Effects of short-term Nordic walking training on sarcopenia-related parameters in women with low bone mass: a preliminary study - Ossowski ZM (Dove Medical Press, 2016)
Zbigniew Marcin Ossowski,1 Wojciech Skrobot,2 Piotr Aschenbrenner,3 Vida Janina Cesnaitiene,4 Miroslaw Smaruj3 1Department of Health Promotion, 2Department of Kinesiology, 3Department of Physical Education, Gdansk University of Physical Education and Sport, Gdansk, Poland; 4Department of Health, Physical and Social, Lithuanian Sports University, Kaunas, Lithuania Background: Several studies have demonstrated the positive effects of physical activity on skeletal muscle mass and muscle strength in women with osteoporosis. However, the impact of Nordic walking training on sarcopenia-related parameters in women with low bone mass remains unknown. Therefore, the purpose of this study was to evaluate the impact of 12 weeks of Nordic walking training on skeletal muscle index, muscle strength, functional mobility, and functional performance in women with low bone mass. Materials and methods: The participants were 45 women, aged 63–79 years, with osteopenia or osteoporosis. The subjects were randomly assigned either to an experimental group (12 weeks of Nordic walking training, three times a week) or to a control group. Skeletal muscle mass and other body composition factors were measured with octapolar bioimpedance InBody 720 analyser. Knee extensor and flexor isometric muscle strength were measured using Biodex System 4 Pro™ dynamometers. This study also used a SAEHAN Digital Hand Dynamometer to measure handgrip muscle strength. The timed up-and-go test was used to measure functional mobility, and the 6-minute walk test was used to measure functional performance. Results: Short-term Nordic walking training induced a significant increase in skeletal muscle mass (P=0.007), skeletal muscle index (P=0.007), strength index of the knee extensor (P=0.016), flexor (P<0.001), functional mobility (P<0.001), and functional performance (P<0.001) and a significant decrease in body mass (P=0.006), body mass index (P<0.001), and percent body fat (P<0.001) in participants. Regarding handgrip muscle strength, no improvement was registered (P=0.315). No significant changes in any of the analyzed parameters were observed in the control group. Conclusion: Overall, short-term Nordic walking training induces positive changes in knee muscle strength and functional performance in women with low bone mass. This finding could be applied in clinical practice for intervention programs in women with osteopenia and osteoporosis. Keywords: aerobic exercise, osteoporosis, muscle mass, strength, postmenopausal